Extensively drug-resistant Pseudomonas aeruginosa: clinical features and treatment with ceftazidime/avibactam and ceftolozane/tazobactam in a tertiary care university hospital center in Portugal – A cross-sectional and retrospective observational study - Mendes Pedro, Diogo; Paulo, Sérgio Eduardo; Santos, Carla Mimoso; Fonseca, Ana Bruschy; Melo Cristino, José; Pereira, Álvaro Ayres; Caneiras, Cátia (Frontiers in Microbiology, 2024)
Extensively drug-resistant Pseudomonas aeruginosa (XDR-PA) is a growing concern due to its increasing incidence, limited therapeutic options, limited data on the optimal treatment, and high mortality rates. The study aimed to characterize the population, the outcome and the microbiological characteristics of XDR-PA identified in a Portuguese university hospital center. One hundred seventyeight individual episodes among 130 patients with XDR-PA detection were identified between January 2019 and December 2021. XDR-PA was defined as resistance to piperacillin-tazobactam, third and fourth generation cephalosporins, carbapenems, aminoglycosides and fluoroquinolones. A retrospective analysis of the medical records was performed. The most common sources of infection were respiratory (32%) and urinary tracts (30%), although skin and soft tissue infections (18%) and primary bacteremia (14%) were also prevalent. Colonization was admitted in 64 cases. Several patients had risk factors for complicated infections, most notably immunosuppression, structural lung abnormalities, major surgery, hemodialysis or foreign intravascular or urinary devices. XDR-PA identification was more frequent in male patients with an average age of 64.3±17.5 years. One nonsusceptibility to colistin was reported. Only 12.4% were susceptible to aztreonam. Ceftazidimeavibactam (CZA) was susceptible in 71.5% of the tested isolates. Ceftolozane-tazobactam (C/T) was susceptible in 77.5% of the tested isolates. Antibiotic regimens with XDR-PA coverage were reserved for patients with declared infection, except to cystic fibrosis. The most frequently administered antibiotics were colistin (41 cases), CZA (39 cases) and C/T (16 cases). When combination therapy was used, CZA plus colistin was preferred. The global mortality rate among infected patients was 35.1%, significantly higher in those with hematologic malignancy (50.0%, p<0.05), followed by the ones with bacteremia (44.4%, p<0.05) and those medicated with colistin (39.0%, p<0.05), especially the ones with respiratory infections (60.0%). Among patients treated with CZA or C/T, the mortality rate seemed to be lower. XDR-PA infections can be severe and difficult to treat, with a high mortality rate. Even though colistin seems to be a viable option, it is likely less safe and efficient than CZA and C/T. To the best of the authors' knowledge, this is the first description of the clinical infection characteristics and treatment of XDR-PA in Portugal.